Calculus : early transcendentals - Guichard, David; Lyryx Learning; Open Textbook Library; BC Open Textbook Project; BCcampus (Lyryx, 2016)
"In 2013, Lyryx forked the now-popular Calculus open textbook written by David Guichard. Michael Cavers of the University of Calgary, together with the Lyryx editorial team, further redeveloped the content, examples, diagrams, and overall look-and-feel of the book, making it more accessible to first year college and university students. Additional contributors have helped improve the content, including Mark Blenkinsop of Carleton University. In particular, there was the addition of an introductory chapter reviewing the fundamental topics required in a first semester Calculus course, and the paring down of topics that are typically beyond the scope of math and engineering service courses. Currently, the book covers the standard Calculus I and II courses, with Calculus III under development."--Open Textbook Library.
Review -- Functions -- Limits -- Derivatives -- Applications of derivatives -- Integration -- Techniques of integration -- Applications of integration -- Sequences and Series -- Differential equations -- Polar coordinates, parametric equations 405 -- Three Dimensions -- Partial Differentiation -- Multiple Integration -- Vector Functions -- Vector Calculus
This work is licensed under the Creative Commons Attribution-NonCommercial-ShareAlike License.
This bibliographic record is available under the Creative Commons CC0 "No Rights Reserved" license.
Creative Commons License (CC BY-NC-SA): This text, including the art and illustrations, are available under the Creative Commons license (CC BY-NC-SA)
Description based on online version; Title from PDF (viewed on February 27, 2017)
Keywords: Calculus -- Textbooks; Electronic books